Scientific Pedagogical Basis Of Improving The Pedagogical System In Developing The Quality Of Physical Endurance At Students - Khudoiberganov Javlonbek Soatboy oglu (International Journal on Human-Computing Studies, 2022)
This article summarizes the scientific and pedagogical basis for improving the pedagogical system in the development of physical endurance qualities in student youth.